Studi Etnobotani dan Identifikasi Tumbuhan Berkhasiat ObatMasyarakat Sub Etnis Wolio Kota Baubau Sulawesi Tenggara - Agus Slamet; S. Hafidhawati Andarias (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The usage of plants as traditional medicine had been known since long time ago by community of Wolio sub ethnic. It had been inherited from generation to generation.  Yet, this time, the knowledge of medicinal plants in community of Woliosub ethnic become more scarce and feared would be disappear as the knowledge of the medicinal plants tended to known only by a group or certain society. This study aimed to documented the kinds of medicinal plants that utilized by community of Wolio Sub ethnic, which expected would become a foundation to conserve ethnobotanical heritage, knowledge and practice of its usage especially at Baubau and other regions generally. At the same time, it can become scientific information materials in the development of research and usage of medicinal plants to obtain biochemical components that could be accountable scientifically. This study used exploration method that was descriptive. The research phase incuding: the determination of key informants namely traditional healer (bhisa) from Wolio sub ethnic and field observation used cruise method. Then, every kind of plants that utilize as ingredients of traditional medicines was recorded it local names, kind of diseases that cured, used part, way and preparation method, single use or mixed (with other additions), giving way and scientific name identification. Collected data were analyzed descriptively. The results showed that there were 122 species and 57 families of plant that utilized as traditional medicines. Part that mostly used was leaf and the less were bud and cambium. The most common processing way was boiled then drunk.